Using the Process-Genre Approach to Improve Fourth-Grade EFL Learners' Paragraph Writing - Héctor Mauricio Arteaga Lara (Universidad de La Sabana, 2018)
Writing plays a significant role in language learning. Previous research has reported on the effectiveness of several approaches to develop writing skills to enhance writing competence, but little attention has been given to the paragraph writing of elementary students. The present qualitative action research study used artifacts, teacher's journals, learner's journals, and a focus group interview to collect data on the way the process-genre approach assisted fourth-grade EFL learners in writing well-structured narrative paragraphs. Data were analyzed using the grounded theory approach, showing that most of the participants managed to write well-structured paragraphs in which they developed only one idea and supported it without deviating from the subject. Learners also became aware of the role of the audience and the features of the narrative writing genre. The findings of the study lend support to the notion that the process-genre approach is an effective way for young learners to achieve the expected goal; hence, it could be more widely adopted in writing courses at the elementary school level.